Pregled metod štetja kupčkov iztrebkov za ocenjevanje številčnosti rastlinojedih parkljarjev - Kavčič, Irena (Zbornik gozdarstva in lesarstva, 2010)
Knowledge of abundance and local densities of deer populations is important inmanagement as well as in biological context. Faecal pellet-group count method, widely used around the world for estimating deer numbers, has been almost neglected in our country. Therefore, we have prepared a comprehensive overview of the method with recommendations for Slovenia to enhance its use. In principle, there are two ways to perform the faecal pellet-group count method, i.e. clearance plot and standing crop method. The latter is not recommended in a daily management practice, as it requires faecal pellet-groupdecay rate estimation, which is rather season and microhabitat specific. Sampling can be done on sampling plots of different shapes and sizesor with the line transect method. Sampling design depends on expected deer densities and ground cover dependent pellet-group detectability. Since distinct habitats are used differentially by the deer, study area stratification on specific habitat types regarding the expected deer densitiesis recommended. Within the species, defecation rates (i.e. number of pellet-groups per day) vary according to season, animal age and gender; nevertheless, due to comparative reasons we recommend the use of constant defecation rates (i.e. 25 for the red deer, 20 for the roe deer, respectively). Moreover, multiple samplings are needed to cover seasonal variety in habitat use. Sampling design is of a major importance for the success of the method and has the biggest impact on the precision of deer numbers/densities estimates, therefore much effort should be devoted to this stage.
Keywords: iztrebki; metode; prežvekovalci; velikost populacije